Healthy Eating Active Living (HEAL) United: Measurably Improving Children's Health. (4th March 2022) - Bryan, Charity; Sims, Sandra; Dunaway, Donna L.; Hester, Donna J.
Abstract: The purpose of this article is to provide an overview of the Health Eating Active Living (HEAL) United Curriculum and how HEAL United is leveraging their advocacy efforts to help K-12 students in Alabama live healthier lives.